Spatio-temporal assessment of infant mortality rate in India - Amitha Puranik; V S Binu; Seena Biju; Sonu H Subba (Wolters Kluwer Medknow Publications, 2018)
Background: Infant mortality rate (IMR) is globally identified by the policymakers as the marker of health of a population. Objectives: This study aimed to detect the change in hotspots of IMR in Indian states from the year 2000 to 2012, identify hotspots of IMR at district level in selected states from each of the six regions of India and determine the potential predictors of IMR after accounting for spatial autocorrelation. Methods: Ecological study design was used to analyze state and district level data on IMR of India. For the first objective, the data were obtained from Sample Registration System. For the second objective, we classified India into six regions and selected a state in each region that had the highest IMR. The district level data on IMR and potential predictors were obtained from surveys, namely, Annual Health Survey, District Level Household and Facility Survey and Census. Spatio-temporal hotspots of IMR were examined using local indicators of spatial association statistic. Spatial regression was used to identify the potential predictors of IMR after accounting for spatial autocorrelation. Results: Temporal hotspots of IMR were found in the central part of India. Spatial hotspots were identified in districts of Uttar Pradesh. A negative association of IMR existed with female literacy rate, mothers receiving antenatal checkup (%), and people living in urban areas (%). Conclusion: IMR continues to be a problem in the states that have previously shown to be poor performing. Certain districts within these states need emphasis for focused activities.